Pengaruh Struktur Modal dan Pengungkapan Corporate Social Responsibility (CSR) terhadap Kinerja Keuangan Perusahaan Industri (Sektor C) yang Terdaftar di BEI Tahun 2021-2023 - Januar Panjaitan; Usep Syaipudin; Ade Widiyanti (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the effect of capital structure and Corporate Social Responsibility (CSR) disclosure on the financial performance of industrial sector C IDX-IC companies listed on the Indonesia Stock Exchange during 2021–2023. Capital structure is proxied by the ratio of long-term debt to equity, while financial performance is measured using Return on Assets (ROA). A quantitative approach with multiple linear regression analysis was employed, and the sample was selected using purposive sampling. The results reveal that capital structure has a significant positive effect on ROA, whereas CSR disclosure has a significant negative effect on ROA. These findings suggest that strategic use of long-term debt can enhance profitability, while the costs and commitments arising from CSR disclosure may reduce financial performance. The study implies that company management should optimize capital structure and carefully balance sustainability strategies through CSR disclosure to avoid diminishing profitability.